Matériel culture : the archaeology of twentieth-century conflict - Schofield, A. J.; Johnson, William Gray, 1957-; Beck, Colleen M. (One world archaeology, 2002)
Should we keep the physical evidence of conflicts and wars? This collection challenges our perception of cultural heritage, with essays investigating among others Cambodia, the Berlin Wall and concentration camps.